Конец среднего палеолита на Русской равнине в свете материалов стоянки Шлях - Нехорошев, П.Е. (Археологический альманах, 2009)
On the basis of the available archaeological and natural science evidence layers 8 and 9 of Shlyakh (Middle Don, Russia) can securely be dated to the end of the Middle Palaeolithic time, to 40-42 kya and 42-44 kya, respectively. A similar age can be supposed for the two uppermost layers of Belokuzminovka (Donbass, Ukraine) and layer 5b of Biryuchaya balka 2 (Lower Don, Russia), which show the closest technological and typological analogies to Shlyakh. It is just about that time and even somewhat earlier that the full-fledged Upper Palaeolithic industries of Kostenki 14, layer IVb, and Kostenki 17, layer II, had already appeared in the Middle Don basin. This means that some Middle Palaeolithic assemblages of the Russian Plain were coeval with or even somewhat younger than the earliest Upper Palaeolithic sites. Therefore, there are grounds to state that the Middle Don region too witnessed the co-existence of Middle and Upper Palaeolithic cultures, as was the case also in the Crimea and Spain.